Service-oriented Controllable Multicast Model for Next Generation Internet - Ye Zhao; Hu Jinlong; Zhang Ling (Institute of Advanced Engineering and Science, 2013)
With the development of the IPv6 networks, more and more applications put forward to use multicast. Multicast security and management is one of the key issues for IP multicast services deployment in IPv6 network as in IPv4 network. We introduce the idea of Service-Oriented Architecture (SOA) in software scope to multicast service, and design a Service-oriented Controllable Multicast Model (SOCMM) for IPv6 multicast services. And the reference implementation of this model is proposed in this paper. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2207